Release Kinetics of Si, Al, Fe, and Mn from Acid Soils in the Presence of EGCG. Issue 10 (31st May 2017) - Yuan, Da-Gang; Deng, Yong-Gang; Pu, Guang-Lan; He, Gang; Zhang, Jun-Si; Weng, Qian; Wang, Chang-Quan
ABSTRACT: Plant polyphenols can affect soil processes. In the present study, batch experiments were conducted to study the effects of epigallocatechin gallate on the release kinetics of silicon (Si), aluminum (Al), iron (Fe), and manganese (Mn) from acid Anthrosol and Luvisol. The results indicated that the optimal model describing the release kinetics of these elements was a double constant, simple Elovich, or parabolic diffusion equation, and a first-order equation was not suitable. These elements went through an initial rapid-release phase, followed by a slower-release phase. The order of release amounts and rates for Anthrosol was Si > Al > Fe > Mn, but they were different at different phases. However, the order for Luvisol was always Al > Mn > Si > Fe. Meanwhile, the release amount and rate of every element was in the order Luvisol > Anthrosol. The results of this study could help to resolve Al and Mn toxicity in acid soils.